Persistent Luminescence: In Vivo Repeatedly Charging Near‐Infrared‐Emitting Mesoporous SiO(2)/ZnGa(2)O(4):Cr(3+) Persistent Luminescence Nanocomposites (Adv. Sci. 3/2015) - Li, Zhanjun (Adv Sci (Weinh), 2015)
Near‐infrared (NIR) persistent luminescence is an exciting phenomenon in which phosphors can continue to emit photons for weeks after excitation ceases. In article number 1500001, Gang Han and co‐workers report a simple, one‐step mesoporous template method for creating NIR‐emitting nanocomposites based on zinc and gallium. The authors find that the persistent luminescence of the nanocomposites could be repeatedly recharged using white light from a light‐emitting diode (LED) in both a simulated deep‐tissue environment and a live mouse model. This concept paves the way to application of such nanocomposites in the fields of photonics and biophotonics. [Image: see text]